Judicial Resolution of Hibah (Gift) over Encumbered Property: An Analysis of the Abdul Hamid Masidullah v. Norehan Abdul Jabbar Case - Noor Lizza Mohamed Said; Muhamad Mu'izz Abdullah; Adnan Mohamed Yusoff (Institut Agama Islam Negeri (IAIN) Bengkulu, 2026)
Tier 2